PENGARUH RISIKO INVESTASI, INVESTMENT OPPORTUNITY SET DAN FIRM SIZE TERHADAP RETURN SAHAM PADA PERUSAHAAN YANG TERGABUNG DALAM INDEKS KOMPAS 100 DI BEI - admin, LINA APRIYANTI B11112038 (Jurnal Manajemen Update, 2016)
This research aims to examine and analyze the effects of Investment Risk, Investment Opportunity Set (IOS) and Firm Size on Stock Return of companies incorporated in Kompas 100 Index Listed On Indonesia Stock Exchange (IDX) over period 2010-2014. Independent variables used are Investment Risk, Investment Opportunity Set (IOS) and Firm Size. The dependent variable used is Stock Return. The kind of this research is quantitative research. The research population covers all of Companies Incorporated in Kompas 100 Index Listed on Indonesia Stock Exchange (IDX). Sample was collected by purposive sampling method. The data of the research population as many as 100 companies, and obtained a sample of 30 companies for 5 years. The analysis technique used was the multiple linear regression, used SPSS program with the simultaneous test (Test F), and the partial test (t test). The results showed that the Investment Opportunity Set (IOS) significantly with the direction of a positive coefficient on Stock Return, Firm Size significantly influence the direction of the negative coefficient on Stock Return, and Investment Risks effect is not significant with a positive coefficient direction toward Stock Return. The ability of the three variables in explaining the effect of the Stock Return of 0.052 or 5.2% indicated by the adjusted R-square, while the remaining 94.8% is influenced by other factors that not included in this research model. Company managers and investors who expect the Stock Return need to pay attention Investment Opportunity Set (IOS), as Investment Opportunity Set (IOS) most influential and significant impact on the magnitude of Stock Return, then Firm Size and Investment Risk. Keywords: Investment Risk, Investment Opportunity Set (IOS), Firm Size and Stock Return.